The strategies of television broadcast during the Covid-19 pandemic: a case study on Indonesian television - Geni, Gammara Lenggo; Briandana, Rizki; Umarella, Farid Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to analyse the media management strategy of Indonesian television stations during the Covid-19 pandemic. In March 2020, an outbreak of the Covid-19 pandemic in Indonesia affected the operations of broadcasting offices, which forced people to work from home. This situation affects the operations, strategy, and content of the television industry. The object of research is Kompas TV, one of the largest media companies in Indonesia, which was the first to implement a digital concept for its customers. The concepts of planning, organising, actuating, and controlling are used to analyse the strategies media utilised. The methodology employed for the current research takes the form of a case study by adopting the qualitative approach through an in-depth interview and observation. The results showed that Kompas TV, through its digital platform in the form of websites, YouTube channels, and social media, achieved an increase in the number of viewers, users, and engagement during the pandemic. In particular, the digital aspect does not only appear in communication, but also in the implementation of the Kompas TV strategy. The results of the study also revealed that strategies carried out on Kompas TV can be used as a model for other television in Indonesia to emulate, in order to sustain its business in times of crisis.